1985
DOI: 10.3382/ps.0640119
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Protein Relationships in the Broiler

Abstract: Male broiler chicks were fed ad libitum diets containing 18, 23, or 30% protein for 3 weeks. In addition, chicks were fed diets containing 12, 23, or 30% protein on a 3-day rotation. Finally, chicks were fed either the 23 or 30% protein on a schedule of 2 days on feed and 1 day off feed. These feeding schemes allowed chicks to consume low to excess protein coupled with either adequate or inadequate energy intake. Feed intakes were equal for the 18, 23, and rotational percent protein dietary groups and lower (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 12 publications
4
38
2
1
Order By: Relevance
“…Several authors (Fanche & Jensen 1989;Rosebrough & McMurtry 1993) observed that chicks fed low-protein diets had a concomitant increase in carcase fat deposition and, as the liver is the primary site of lipogenesis in chickens (Rosebrough & Steele 1985) the increase of liver percentage observed by the same authors, suggests that the tendency for increased liver weight in chick fed low-protein diets can be related to an increase in lipogenetic activity. In our trial, in general, there are few differences among groups in terms of fat deposition and percentage of liver.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors (Fanche & Jensen 1989;Rosebrough & McMurtry 1993) observed that chicks fed low-protein diets had a concomitant increase in carcase fat deposition and, as the liver is the primary site of lipogenesis in chickens (Rosebrough & Steele 1985) the increase of liver percentage observed by the same authors, suggests that the tendency for increased liver weight in chick fed low-protein diets can be related to an increase in lipogenetic activity. In our trial, in general, there are few differences among groups in terms of fat deposition and percentage of liver.…”
Section: Discussionmentioning
confidence: 98%
“…Broiler chickens fed increasing energy levels (from 2600 to 3200 kcal ME kg -1 ) showed no significant effects on performance parameters, although there was a decrease in feed intake and an improvement in feed conversion with increasing dietary levels (Waldroup et al, 1990;Attia et al, 2001). Animals fed low energy diets try to obtain adequate energy intake by increasing feed consumption (Rosebrough and Steele, 1985;NRC, 1994). Ghazanfari et al, (2010) reported feed intake and body weight gain increased in broiler fed on low-energy diets compared with those fed on high energy diets during different periods.…”
Section: Growth Performancementioning
confidence: 99%
“…Excessive energy intake is related to the calorie:protein (c:p) ratio in the diet, and consequently, to carcass composition. Isocaloric diets with decreasing protein levels show increasing c:p ratio, which result in carcasses with higher fat percentage (Donaldson, 1985;Rosebrough and Steele, 1985). Armstrong and Britt (1987) showed that changes in energy and protein levels in diets are associated with increased or decreased levels of the concentrations of growth hormone in the blood serum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no interaction between dietary energy and protein on blood characteristics, but dietary energy increased from 3,100 to 3,200 kcal/kg in the diet had increased serum glucose level from 237.16 to 281.28 mg/dL (Table 6). So it can be assumed that increased dietary ME and CP increases serum glucose level via two processes (1) an enhancement of de novo lipogenesis (Rosebrough andSteele. 1985, Swennen et al, 2005) and (2) a decreased whole body fat oxidation consecutive to the rise in carbohydrate oxidation (Shah and Garg, 1996).…”
Section: Dietary Protein and Carbohydrate Has An Important Impactmentioning
confidence: 99%